An Ostomy Self-management Telehealth Intervention for Cancer Survivors: Technology-Related Findings From a Randomized Controlled Trial - Ronald S Weinstein; Michael J Holcomb; Julia Mo; Peter Yonsetto; Octavio Bojorquez; Marcia Grant; Christopher S Wendel; Nancy J Tallman; Elizabeth Ercolano; Zuleyha Cidav; Mark C Hornbrook; Virginia Sun; et al. (JMIR Publications, 2021)
BackgroundAn Ostomy Self-management Telehealth (OSMT) intervention by nurse educators and peer ostomates can equip new ostomates with critical knowledge regarding ostomy care. A telehealth technology assessment aim was to measure telehealth engineer support requirements for telehealth technology-related (TTR) incidents encountered during OSMT intervention sessions held via a secure cloud-based videoconferencing service, Zoom for Healthcare. ObjectiveThis paper examines technology-related challenges, issues, and opportunities encountered in the use of telehealth in a randomized controlled trial intervention for cancer survivors living with a permanent ostomy. MethodsThe Arizona Telemedicine Program provided telehealth engineering support for 105 OSMT sessions, scheduled for 90 to 120 minutes each, over a 2-year period. The OSMT groups included up to 15 participants, comprising 4-6 ostomates, 4-6 peer ostomates, 2 nurse educators, and 1 telehealth engineer. OSMT-session TTR incidents were recorded contemporaneously in detailed notes by the research staff. TTR incidents were categorized and tallied. ResultsA total of 97.1% (102/105) OSMT sessions were completed as scheduled. In total, 3 OSMT sessions were not held owing to non-technology-related reasons. Of the 93 ostomates who participated in OSMT sessions, 80 (86%) completed their OSMT curriculum. TTR incidents occurred in 36.3% (37/102) of the completed sessions with varying disruptive impacts. No sessions were canceled or rescheduled because of TTR incidents. Disruptions from TTR incidents were minimized by following the TTR incident prevention and incident response plans. ConclusionsTelehealth videoconferencing technology can enable ostomates to participate in ostomy self-management education by incorporating dedicated telehealth engineering support. Potentially, OSMT greatly expands the availability of ostomy self-management education for new ostomates. Trial RegistrationClinicalTrials.gov NCT02974634; https://clinicaltrials.gov/ct2/show/NCT02974634